2012
DOI: 10.7824/rbh.v11i1.159
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de herbicidas utilizados no algodoeiro para o controle de Amaranthus

Abstract: Some species of Amaranthus are widely distributed in cotton crops. In recent years, ineffective weed control after herbicide use of some species has been reported. The current study was installed in order to find effective alternatives to a proper management of these species. Two simultaneous experiments were carried out for each species in this study (Amaranthus lividus and Amaranthus hybridus), and in each of them, a different stage of weed development (2 to 4 and 4 to 6 leaves) was focused. Twenty two herbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Even after finding A. retroflexus biotypes with cross-resistance and multiple resistance to ALS-and PS II-inhibiting herbicides used in the sampled areas, either in preemergence or postemergence, it was observed that an effective control can be achieved with S-metolachlor, diuron and trifluralin in preemergence. Other choices for an effective control of other Amaranthus species such as A. lividus and A. hybridus are glufosinate-ammonium and glyphosate (Braz et al, 2012). However, the use of these herbicides in postemergence requires the use of tolerant cultivars to these herbicides.…”
Section: Als Inhibitors (Trifloxysulfuron-sodium and Pyrithiobac-sodium)mentioning
confidence: 99%
“…Even after finding A. retroflexus biotypes with cross-resistance and multiple resistance to ALS-and PS II-inhibiting herbicides used in the sampled areas, either in preemergence or postemergence, it was observed that an effective control can be achieved with S-metolachlor, diuron and trifluralin in preemergence. Other choices for an effective control of other Amaranthus species such as A. lividus and A. hybridus are glufosinate-ammonium and glyphosate (Braz et al, 2012). However, the use of these herbicides in postemergence requires the use of tolerant cultivars to these herbicides.…”
Section: Als Inhibitors (Trifloxysulfuron-sodium and Pyrithiobac-sodium)mentioning
confidence: 99%
“…Um fator determinante para o controle de plantas daninhas é o estádio no qual elas se encontram no momento da aplicação (Braz et al, 2012). A ineficiência do glyphosate pode ser devido ao estádio de desenvolvimento das plantas de M. nudiflora que estavam em pleno florescimento quando recebeu a aplicação dos tratamentos e também a dose utilizada.…”
Section: Resultados E Discussão Experimento 1 Eficácia Dos Herbicidasunclassified